Pengaruh Beban Kerja, Skeptisme Profesional, dan Pengalaman Auditor dalam Mendeteksi Kecurangan dengan Pelatihan Audit Kecurangan sebagai Variabel Moderasi - Harry Budiantoro; Meilisa Nurrahmah; Kanaya Lapae (Journal of Business and Economics Research (JBE), 2022)
The purpose of this study is to see how workload, professional skepticism, and audit experience affect the auditor's ability to detect fraud, with fraud audit training as a moderating variable. This research was conducted at a Public Accounting Firm (KAP) in the Jakarta area. This study uses primary data obtained directly through a questionnaire. Multiple linear regression was used as the analytical method. The results showed that Professional Skepticism and Audit Experience had a significant effect on the Auditor's Ability to Detect Fraud, but Workload had no significant effect. Workload, Professional Skepticism, and Audit Experience all have a significant impact on the auditor's ability to detect fraud simultaneously. Fraud Audit Training also proved ineffective in moderating the relationship between Professional Skepticism and Auditor Ability to Detect Fraud, but proved effective in moderating the relationship between Workload and Audit Experience on Auditor Ability to Detect Fraud..